Application Of Nanofiltration In Metal Recovery - I. W. van der Merwe (The Southern African Institute of Mining and Metallurgy, 1998)
Recently, a new kind of filtration has emerged, namely nano-filtration (NF). It is a membrane-based process which exhibits totally unique separation characteristics for dissolved salts as well as for many non-charged species. By exploiting the particular separation characteristics of this new membrane type, many unique and novel separations have been made possible. The basis for separation by nanofiltration is the negative surface charge of the membrane. This results in rejection of multivalent anions, whilst associated cations are also rejected to maintain electro-neutrality. This peculiar property enables separation of dissolved ions such as sulphate and copper from acid, whilst the acid may be purified for reuse. This paper aims at providing an overview of the principles of nanofiltration, illustrated by particular examples.